2020
DOI: 10.1172/jci.insight.137969
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 scaffolding domain peptide regulates glucose metabolism in lung fibrosis

Abstract: startup biotechnology firm that is commercializing CSP7 for the treatment of IPF. SS has patents (patent no. 8697840 B2, "Peptide Inhibition of Lung epithelial Apoptosis and Pulmonary Fibrosis" and patent no. 9,630,990, "Inhibition of Pulmonary Fibrosis with Chemical and Peptide Inhibitors") issued for the use of the caveolin-1 scaffolding domain peptide and its fragments for the treatment of lung injury and lung fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Accumulating studies have demonstrated hypoxia could significantly affect metabolic phenotype in cancer cells [ 20 , 21 ]. The association of hypoxia or HIF-α with altered metabolism in cardiovascular [ 22 , 23 ] and fibrotic disorders [ 24 ] was also reported. Many studies demonstrated that chronic hypoxia triggers signaling pathways that regulate cardiac metabolic remodeling, particularly at the transcriptional level, to maintain energy production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating studies have demonstrated hypoxia could significantly affect metabolic phenotype in cancer cells [ 20 , 21 ]. The association of hypoxia or HIF-α with altered metabolism in cardiovascular [ 22 , 23 ] and fibrotic disorders [ 24 ] was also reported. Many studies demonstrated that chronic hypoxia triggers signaling pathways that regulate cardiac metabolic remodeling, particularly at the transcriptional level, to maintain energy production.…”
Section: Introductionmentioning
confidence: 99%
“…He et al reported elevated HIF-1α expression and altered endothelial metabolism, including increased glycolysis and reduced oxygen consumption in the endothelium of coronary arteries after mice were treated with a PHD inhibitor, dimethyloxalylglycine. Gopu et al [ 25 ] observed increased basal expression of HIF-1α and glycolytic enzymes as well as lactate and succinate levels in fibrotic lung fibroblasts compared with normal lung fibroblasts. Keloids typically feature excessive proliferation of fibroblasts and deposition of ECM and microvascular abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that CAV1 scaffolding domain may be critical in controlling the dynamic phenotype of cancer cells by facilitating the interaction of specific signal transduction pathways [58]. The peptide was able to competitively bind with various signal molecules and interrupt their interaction with CAV1 in vivo, exhibiting multiple biological activities [59][60][61]. The above findings suggest that the scaffolding domain might be a promising target for therapy of various diseases.…”
Section: Discussionmentioning
confidence: 89%
“…Although metabolic change is a field modestly addressed in idiopathic pulmonary fibrosis, it is involved in the survival of cells against nutrient stress, differentiation to myofibroblasts and collagen production [ 106 , 127 , 128 ]. Lactic acid, from anaerobic metabolism, has been proposed as an important mediator of myofibroblast differentiation through the pH-dependent activation of TGF-β [ 129 , 130 ]. Myofibroblasts from IPF have increased glycolysis and increased differentiation, mediated by HIF-1α and TGF-β [ 131 ].…”
Section: Hypoxia Signaling Overlap In Cancer and Fibrosis?mentioning
confidence: 99%